A workplace curriculum and strategies to enhance learning experiences for machining workers - Mohd Yunus, Azmir; Bakar, Ab. Rahim; Hamzah, Azimi; Wan Jaafar, Wan Marzuki (Macrothink Institute, 2016)
Existing literature seldom discusses curricula and strategies used by employers to train workers who lack initial training for the occupations in which they are employed. This paper aims to add to this discussion within the context of skill formation for machining workers. The site of the study was a car engine factory in Malaysia. Using a qualitative case study methodology, data were obtained through interviews with the factory manager and trainers, observation of the factory and its training facility, and documents relating to training. The findings show that skill formation is planned as a gradual process. A gradual progression pathway was put in place to serve as both a career track and a learning track for workers. In order to enhance workers’ learning experiences, the factory ensures that (1) workers have sufficient mathematical skill, (2) syllabus and training modules are used for training, (3) training is designed to maximize opportunities for practice, and (4) workers’ skills are continuously assessed.